Penerapan Model STAD untuk Meningkatkan Keaktifan Belajar PAI Siswa Kelas VII SMPN 1 Tembelang - Aisyatul Izzah Putri Aini; Chusnul Chotimah; Hidayatur Rohmah (YASIN, 2026)
Although cooperative learning models have received attention in various previous studies, research that specifically discusses the implementation of the Student Team Achievement Division (STAD) model in improving learning activeness in Islamic Education (PAI) at the junior secondary school level still requires further exploration. This study aims to analyze the implementation of the STAD-type cooperative learning model in improving students’ learning activeness in the PAI subject. This study used a qualitative approach with a descriptive design, involving informants consisting of the principal, vice principal for curriculum, PAI teacher, and students of Class VII D at SMP Negeri 1 Tembelang. Data were collected through observation, interviews, and documentation, and were then analyzed using qualitative data analysis techniques. The results showed that the implementation of the STAD learning model was effective and able to improve students’ learning activeness, as reflected in the increased participation of students in discussions, asking questions, and the courage to express opinions during the learning process. These findings contribute to strengthening cooperative learning theory and expanding understanding of strategies to enhance student engagement in the context of religious education. The conclusion of the study emphasizes that systematic steps in STAD, such as class presentation, learning teams, quizzes, progress scores, and rewards, play an important role in creating an interactive and collaborative learning atmosphere. This study also emphasizes the need for effective time management and attention to differences in the level of activeness among students so that the implementation of STAD can proceed optimally.